Journal of Digital Imaging - Honeyman-Buck, Janice C.; Avrin, David; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
The Journal of Digital Imaging (JDI) is the official peer-reviewed journal of the Society for Imaging Informatics in Medicine (SIIM). JDI$1 (Bs goal is to enhance the exchange of knowledge encompassed by the general topic of Imaging Informatics in Medicine such as research and practice in clinical, engineering, and information technologies and techniques in all medical imaging environments. JDI topics are of interest to researchers, developers, educators, physicians, and imaging informatics professionals. Suggested Topics PACS and component systems; imaging informatics for the enterprise; image-enabled electronic medical records; RIS and HIS; digital image acquisition; image processing; image data compression; 3D, visualization, and multimedia; speech recognition; computer-aided diagnosis; facilities design; imaging vocabularies and ontologies; Transforming the Radiological Interpretation Process (TRIP$1!"(B); DICOM and other standards; workflow and process modeling and simulation; quality assurance; archive integrity and security; teleradiology; digital mammography; and radiological informatics education. In each of these areas, technology, economics, novel developments or applications, and educational uses or impacts are all sub-topics. Indexed in: Index Medicus, Current Contents (ISI), Compendex (COM), and Current Index to Nursing and Allied Health (CIN). .s
Keywords: Radiology; Imaging / Radiology